دراسة العلاقة بين البطالة والجريمة حالة الجزائر- خلال الفترة 2001/2010- - ريمي, عقبة; قصاب, سعدية (جامعة الوادي - University of Eloued, 2014)
في الجزائر يلاحظ عدم وجود دراسات تجريبية كثيرة اهتمت بدراسة أثر البطالة على الجريمة، ومن ثم فإن الهدف الرئيسي لهذه الدراسة هو معرفة العلاقة بين معدلات البطالة و معدلات الجريمة في الجزائر، لاختبار فرضية نظرية اقتصاد الجريمة القائلة بأن الزيادة في معدلات البطالة سوف تؤدي إلي زيادة معدلات الجريمة، ولتحقيق هذا الهدف سوف نستخدم معامل الارتباط الخطي البسيط لبيرسون لقياس العلاقة بين معدلات البطالة ومعدلات الجريمة In Algeria, it is noted that there are not many empirical studies to study the impact of unemployment on crime. Therefore, the main objective of this study is to find out the relationship between unemployment rates and crime rates in Algeria to test the hypothesis of the crime economy theory that the increase in unemployment rates will lead to increased rates To achieve this goal, we will use Pearson's simple linear correlation coefficient to measure the relationship between unemployment rates and crime rates
مقال
Keywords: البطالة، الجريمة، معامل الارتباط; Unemployment, crime, correlation coefficient